Cell–matrix feedback controls stretch-induced cellular memory and fibroblast activation - Yuan Hong; Xiangjun Peng; Haomin Yu; Mohammad Jafari; Delaram Shakiba; Yuxuan Huang; Chengqing Qu; Ermia E. Melika; Andrew K. Tawadros; Aliza Mujahid; Yin-Yuan Huang; Jacob A. Sandler; et al. (Proceedings of the National Academy of Sciences, 2025)
Mechanical stretch can activate long-lived changes in fibroblasts, increasing their contractility and initiating phenotypic transformations. This activation, critical to wound healing and procedures such as skin grafting, increases with mechanical stimulus for cells cultured in two-dimensional but is highly variable in cells in three-dimensional (3D) tissue. Here, we show that static mechanical stretch of cells in 3D tissues can either increase or decrease fibroblast activation depending upon recursive cell–extracellular matrix (ECM) feedback and demonstrate control of this activation through integrated in vitro and mathematical models. ECM viscoelasticity, signaling dynamics, and cell mechanics combine to yield a predictable, but nonmonotonic, relationship between mechanical stretch and long-term cell activation. Results demonstrate that feedback between cells and ECM determine how cells retain memory of mechanical stretch and have direct implications for improving outcomes in skin grafting procedures.